Posterior percutaneous endoscopic cervical foraminotomy and discectomy for degenerative cervical radiculopathy using intraoperative O-arm imaging - Shu, Wei (Wideochir Inne Tech Maloinwazyjne, 2019)
INTRODUCTION: Posterior percutaneous endoscopic cervical foraminotomy and discectomy (P-PECD) is a minimally invasive technique for the treatment of degenerative cervical radiculopathy. The O-arm, an intraoperative mobile computed tomography (CT) scanner, may improve spine surgery outcomes. AIM: To evaluate clinical outcomes of O-arm assisted P-PECD in patients with degenerative cervical radiculopathy. MATERIAL AND METHODS: Between January 2013 and January 2018, 32 patients with degenerative cervical radiculopathy who underwent P-PECD were followed up for 12 months. Their demographic, clinical and surgical data were reviewed retrospectively. All patients received intraoperative O-arm scanning to assess working cannula placement and decompression. The visual analogue scale (VAS), the neck disability index (NDI), and Odom’s criteria were used to evaluate clinical outcomes. RESULTS: Compared with preoperative values, mean NDI, neck-VAS, and arm-VAS scores were dramatically improved 1 week postoperatively, and the improvement was maintained for at least a year after surgery (from 27.6 ±10.5, 5.8 ±1.7, and 7.2 ±2.3 to 1.4 ±0.8, 1.1 ±0.8 and 0.9 ±0.6, respectively). According to Odom’s criteria, 27/32 patients (84.4%) reported excellent or good results. There were no permanent complications. One patient suffered from transient thumb weakness due to a cervical nerve root injury caused by the spinal needle. CONCLUSIONS: P-PECD aided by intraoperative O-arm imaging is a safe, effective, and minimally invasive procedure for treating degenerative cervical radiculopathy that can provide accurate cannula placement and thorough decompression.